IL‐8 induces transdifferentiation of mature hepatocytes toward the cholangiocyte phenotype - Tokio Sasaki; Yuji Suzuki; Keisuke Kakisaka; Ting Wang; Kazuyuki Ishida; Akiko Suzuki; Hiroaki Abe; Tamotsu Sugai; Yasuhiro Takikawa (FEBS Open Bio)
The adult mammalian liver exhibits a remarkable regenerative capacity, with different modes of regeneration according to the type and extent of injury. Hepatocyte–cholangiocyte biphenotypic liver progenitor cell populations appear under conditions of excessive injury. It has been reported that mature hepatocytes can transdifferentiate toward a cholangiocyte phenotype and be a cellular source of progenitor cell populations. Here, we determined that among various plasma cytokines, interleukin (IL)‐8 levels were significantly elevated in acute liver failure and severe acute liver injury patients. In vitro assays revealed that administration of IL‐8 homologues increases the expression of Sry HMG box protein 9 (SOX9). In liver biopsies of acute liver injury patients, we observed the appearance of SOX9‐positive biphenotypic hepatocytes accompanied by elevation of plasma IL‐8 levels. Our results suggest that IL‐8 regulates the phenotypic conversion of mature hepatocytes toward a cholangiocyte phenotype.